A sweet decision: treatment of stable coronary artery disease in patients with diabetes mellitus - Sinning, Christoph; Westermann, Dirk (Annals of Translational Medicine, 2017)
The numbers of patients with coronary artery disease (CAD) are increasing globally and stable CAD with its symptoms of angina pectoris and increased risk of coronary events despite decreasing mortality is a serious health problem (1). Especially patients with diabetes mellitus are at high risk for development of CAD as well as subsequent coronary events associated with high mortality (2). Indeed, the extent of CAD seems to be increasing faster in patients with diabetes mellitus compared to patients without it independent of other classical risk factors. Therefore, patients with CAD and diabetes mellitus are at exceptional risk and are thought to need best medical as well as revascularization treatment (3). Nevertheless, little data is available whether treatment decisions need to be tailored to the individual extent of CAD in patients with diabetes mellitus or whether patients need to be treated similar irrespectively of their CAD status.